Docência em Educação Física Inclusiva: esgotamentos vividos no contexto do ensino remoto brasileiro - Machado, Roseli Belmonte (2021)
The year 2020 was marked by the pandemic of Covid-19, a fact that impacted on different aspects of life. The social distancing was one of the ways to contain the pandemic, causing the cessation of face-to-face classes in Brazil, migrating to a remote teaching model. In this reality, this study, which considers remote teaching within the Brazilian social, political, and economic context, aimed to problematize the teaching of Physical Education in the context of remote classes in Brazil, focusing on the work with those considered students of inclusion. It is a qualitative exploratory study, in which interviews with Physical Education teachers were conducted. 116 interviews were carried out through a questionnaire elaborated on the Google platform. The analysis followed the contribution of post-structuralist researches to think about Education, supported by the concepts of governamentality and teaching. From the analysis, two points are brought up for discussion: the practices worked in Physical Education with students of inclusion in remote education, and the idea of teaching crisis in inclusive Physical Education. Thus, it is argued that the lack of contact with students at school and the inequalities in the Brazilian social and economic context can lead to exclusionary practices and contribute to teaching burnout.